Single Step In Situ Synthesis and Optical Properties of Polyaniline/ZnO Nanocomposites. (2nd January 2014) - Sharma, Deepali; Kaith, B. S.; Rajput, Jaspreet
Abstract : Polyaniline/ZnO nanocomposites were prepared by in situ oxidative polymerization of aniline monomer in the presence of different weight percentages of ZnO nanostructures. The steric stabilizer added to prevent the agglomeration of nanostructures in the polymer matrix was found to affect the final properties of the nanocomposite. ZnO nanostructures of various morphologies and sizes were prepared in the absence and presence of sodium lauryl sulphate (SLS) surfactant under different reaction conditions like in the presence of microwave radiation (microwave oven), under pressure (autoclave), under vacuum (vacuum oven), and at room temperature (ambient condition). The conductivity of these synthesized nanocomposites was evaluated using two-probe method and the effect of concentration of ZnO nanostructures on conductivity was observed. X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FTIR), and UV-visible (UV-VIS) spectroscopy techniques were used to characterize nanocomposites. The optical energy band gap of the nanocomposites was calculated from absorption spectra and ranged between 1.5 and 3.21 eV. The reported values depicted the blue shift in nanocomposites as compared to the band gap energies of synthesized ZnO nanostructures. The present work focuses on the one-step synthesis and potential use of PANI/ZnO nanocomposite in molecular electronics as well as in optical devices.